2018
DOI: 10.1186/s12889-018-5972-x
|View full text |Cite
|
Sign up to set email alerts
|

Disease-specific health literacy, disease knowledge, and adherence behavior among patients with type 2 diabetes in Taiwan

Abstract: BackgroundTo examine the association between health literacy, level of disease knowledge, and adherence behavior among patients with type 2 diabetes.MethodsA cross-sectional survey study of 1059 Mandarin- and Taiwanese-speaking patients aged 20 years or older with type 2 diabetes was conducted. The demographic profiles of the sample strata were determined by analyzing the Taiwanese National Health Insurance Database. Participants were enrolled and completed questionnaires between April and November of 2015. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 51 publications
7
46
2
Order By: Relevance
“…Better knowledge contributes to better adherence. This finding was in line with previously reported literature that mentions disease literacy as a determinant of achieving positive treatment outcomes (Yeh et al, 2018;AlQarni et al, 2019). Our findings are in line with the results of Nazir et al (2016) as there was a negative relationship between Hb A1c value and, adherence and disease knowledge in patients with diabetes in Pakistan.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Better knowledge contributes to better adherence. This finding was in line with previously reported literature that mentions disease literacy as a determinant of achieving positive treatment outcomes (Yeh et al, 2018;AlQarni et al, 2019). Our findings are in line with the results of Nazir et al (2016) as there was a negative relationship between Hb A1c value and, adherence and disease knowledge in patients with diabetes in Pakistan.…”
Section: Discussionsupporting
confidence: 92%
“…There is a plethora of studies that highlight the importance of adhering to medications in type 2 diabetes mellitus (Al-Nozha et al, 2004;Abahussain and El-Zubier, 2005;Abbas et al, 2015;Al Dawish et al, 2016). However, it is imperative to improve patients' disease knowledge to achieve high adherence to therapy (Yeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, limited FHL creates considerable challenges even when trying to accomplish simple tasks, such as reading and understanding a consent form or a health education brochure (Baker, Williams, Parker, Gazmararian, & Nurss, 1999). It is also associated with poor understanding of oral instructions (Schillinger, Bindman, Wang, Stewart, & Piette, 2004), low disease knowledge (Yeh et al, 2018) and less use of more effective coping strategies, such as seeking information (Ellis, Mullan, Worsley, & Pai, 2012; Rahmani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy, which is defined as the ability to read, understand, evaluate and use health information to make reasoned, health‐related decisions (Sorensen et al, ), has been reported to be negatively associated with healthcare decision‐making (Seo, Goodman, Politi, Blanchard, & Kaphingst, ; Van der Heide, Uiters, Jantine Schuit, Rademakers, & Fransen, ) and health outcomes including health disparity and mortality (Cutilli, Simko, Colbert, & Bennett, ; Smith, Jackson, Kobayashi, & Steptoe, ). However, another nationwide study reported that although there is a strong relationship between disease‐specific health literacy and knowledge, an association between health literacy and self‐management is not evident (Yeh et al, ). Moreover, evidence of the influence of health literacy on hospice decision‐making is scarce.…”
Section: Introductionmentioning
confidence: 99%